The Influence of Digital Financial Reporting on Transparency Quality: A Signaling Theory Approach - Pradipta, Alya Nur; Putra, Rizky Anwar (Universitas Sains dan Teknologi Komputer, 2025)
The digital transformation has changed the entire view of financial reporting, and, in turn, it has made XBRL-based systems faster, more accurate, and more interactive. On the other hand, digitalization was not an option for all firms in terms of the transparency of substantive information. The research presented here focuses on the impact of digital financial reporting on the transparency quality of publicly listed companies in Indonesia, through the lens of signaling theory, which views digitalization as a signal of management’s credibility and commitment to openness. To carry out the study, a quantitative explanatory approach is adopted, and secondary data comprising 120 IDX-listed companies from the 2022–2024 period is used, which is subjected to Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis. The study demonstrates that digital financial reporting has a strong and significant influence on transparency quality (β = 0.524; p < 0.001), with an R² of 0.456. Accessibility is the most influential factor in increasing transparency, followed by interactivity, standardization, and timeliness. The above-mentioned events make it clear that both access and interactivity are major factors in the public's acceptance and reliance on digital financial reports. The foremost advantage of the current research is the combination of new concepts in digital financial reporting and signaling theory in the context of an emerging market, which provides empirical evidence that digitalization serves as an honesty signal that strengthens corporate reputation, credibility, and governance quality.